Orthodontic treatment of an adult Class II division 1 malocclusion with nonextraction assisted by lip myofunctional training: A case report. Issue 7 (14th April 2020) - Hou, Jianhua; Meng, Xiuping
Abstract: Consideration of facial soft tissue is critical in orthodontic diagnosis and treatment planning to achieve improvement in facial esthetics as well as dental occlusion. As is illustrated by success in orthodontic treatment of an adult Class II division 1 malocclusion with nonextraction and assisted by lip myofunctional training. Abstract : Consideration of facial soft tissue is critical in orthodontic diagnosis and treatment planning to achieve improvement in facial esthetics as well as dental occlusion. As is illustrated by success in orthodontic treatment of an adult Class II division 1 malocclusion with nonextraction and assisted by lip myofunctional training.